High voltage DC-DC converter with standalone application - Babu, Thiruveedula Madhu; Chenchireddy, Kalagotla; Rohini, Jakkani; Suhas, Mesaragandla Sai; Ajitesh, Dara; Rahul, Kanaparthi (International Journal of Applied Power Engineering (IJAPE), 2023)
Designing DC-DC converters involves many voltage lift techniques. These techniques have been encouraged for their credible advantages. Most voltage lifting methods are applied in many areas of automotive, motor drives, telecom and electronic welfare in military applications. Voltage lifting techniques are known for their high voltage transfer gain and high efficiency. Ultra-lift converter yields very high output transfer gain with geometric progression compared to other voltage lift techniques such as super lift converters and classical boost converters. It also offers reduced size and improved efficiency when compared. In this proposed method ultra-lift converter operation is analyzed with continuous conduction mode.